Factors associated with the administration of the municipal share from the 1 percent additional real property tax for public elementary and secondary education an exploratory study - Guillermo, Mariano J. 1931-
The administration of the Special Education Fund established by Republic Act No. 5447, as amended, was studied in a sample of 19 municipalities from Region 8 which were chosen through a combination of cluster and deliberate selection process. A total of 123 members of the school boards, assessors, budget officers and others with vital roles in the assessment, collection and allocation of the Special Education Fund, answered a questionnaire. Stepwise multiple regression analysis revealed that the number of lots declared for taxation purposes, education, class of community, percentage of male over female, updated and well-maintained assessment role and age of respondents were significantly associated with collection efficiency.